AN ANALYSIS OF LANGUAGE PROFICICENCY FOR STUDENTS OF MEDICAL LABORATORY TECHNOLOGY - Juita, Erlinna; Hartini H, Hartini H (English Department, University of Riau Kepulauan, Batam,Indonesia, 2019)
Facing the era of Industrial Revolution 4.0 in which technology has become the daily basis of human life, English has become inevitably significant. In fact, it is really needed in the health sector, especially medical laboratory technology which adopted advanced technology, and thus requires the medical technologist to be able to accomplish human to human and human to machine interactions. This study aimed to identify the language proficiency of students of medical laboratory technology. The population of this study was the students of Akademi Kesehatan John Paul II Pekanbaru. The instrument used in this study is test. The results indicated that the overall performance was still categorized in the lowest level (A2) with the scores ranging from 337 to 443. In the first two sections, listening comprehension and structure and written expression, most of the students’ proficiency was classified in the lowest level (A2) with the scores ranging from 38-49 and 33-43 respectively. In the last section, reading comprehension, all students’ proficiency was classified in the lowest level (A2) with the scores ranging from 31-47. In conclusion, students’ language proficiency was still categorized in the basic level or waystage